Alpha Beta Testing pada Media Pembelajaran Dasar Agama di Lingkungan Tempat Pembelajaran Al-Quran - Khasanah, Fata Nidaul; Prasojo, Prasojo; Untari, Dhian Tyas; Setiyadi, Didik (Journal of Practical Computer Science, 2025)
The rapid development of technology today has significantly influenced educational processes, both formal and non-formal. It has also impacted learning materials and the methods used to deliver them during the teaching and learning process. However, not all educational institutions are able to take advantage of this technological advancement—one example is the Qur'anic Education Center (Tempat Pendidikan Al-Qur’an, or TPA). TPA is a non-formal educational institution in which the learning process predominantly relies on traditional lecture-based methods delivered by instructors. This often results in low student attention and limited understanding of the learning material. To address this issue, an interactive learning media application was designed to support the introduction of basic Islamic religious knowledge. The aim of this research is to test the functionality of the developed learning media application in order to minimize anomalies and ensure usability. One of the suitable software testing approaches used in this context is user acceptance testing. The testing methods implemented in this study include alpha testing and beta testing. The alpha testing results indicate that the application functions as expected for each tested case scenario. Furthermore, the beta testing results showed an average survey score of 82% across the criteria of usability, ease of learning, ease of use, and user satisfaction